KLASIFIKASI DAN ANALISIS KONTEN DAKWAH DI APLIKASI TIKTOK: TEMA DAN BENTUK PENYAMPAIAAN - Alfianti, Amellia; Widayanti, Tri; Assidqiah, Mulhima (MAMBA'UL 'ULUM, 2025)
This study discusses the classification of dakwah content on the TikTok application, which is popular among Indonesian youth. Considering the high number of TikTok users in Indonesia and the dominance of Generation Z as the main users, this research examines dakwah content based on themes, types, and the purpose of messarge delivery. The research method used is a literature study applying dakwah communication theory and new media theory to understand the changing patterns of digital dakwah. The results identify that dakwah content on TikTok includes materials on creed (akidah), Islamic jurisprudence (fiqih), and ethics (akhlak) presented in various formats such as short sermons, religious Q&A, inspirational stories, prayers, humor, and social issues. Digital dakwah on TikTok is interactive, creative, and effective in reaching a young audience, despite challenges such as short duration, virality, ethics, and message misinterpretation. Successful dakwah strategies involve the use of simple language, appealing visuals, active interaction, and the utilization of TikTok features and current trends. This study emphasizes the importance of digital literacy and communication ethics to maintain the quality of dakwah in the social media era.